Suppressive function of androgen receptor in bone resorption - Kawano, Hirotaka (National Academy of Sciences, 2003)
As locally converted estrogen from testicular testosterone contributes to apparent androgen activity, the physiological significance of androgen receptor (AR) function in the beneficial effects of androgens on skeletal tissues has remained unclear. We show here that inactivation of AR in mice using a Cre-loxP system-mediated gene-targeting technique caused bone loss in males but not in females. Histomorphometric analyses of 8-week-old male AR knockout (ARKO) mice showed high bone turnover with increased bone resorption that resulted in reduced trabecular and cortical bone mass without affecting bone shape. Bone loss in orchidectomized male ARKO mice was only partially prevented by treatment with aromatizable testosterone. Analysis of primary osteoblasts and osteoclasts from ARKO mice revealed that AR function was required for the suppressive effects of androgens on osteoclastogenesis supporting activity of osteoblasts but not on osteoclasts. Furthermore, expression of the receptor activator of NF-κB ligand (RANKL) gene, which encodes a major osteoclastogenesis inducer, was found to be up-regulated in osteoblasts from AR-deficient mice. Our results indicate that AR function is indispensable for male-type bone formation and remodeling.